(untitled) (Research, Society and Development, 2026)
This study aims to identify and analyze the Amin behavioral and social difficulties experienced by children in the context of paternal absence, as well as to examine the relationship between the absence of a father figure and school performance. The study analyzes the impacts of paternal absence on the child socialization process in an Angolan urban context, focusing on the Cinco Fios neighborhood in the Kilamba Centrality, Luanda. Based on the premise that the family constitutes the primary agent of primary socialization, the research is framed within the contemporary transformations of family structures, particularly the increase in single-parent families. A quantitative, descriptive, and cross-sectional approach was adopted, applying a structured questionnaire to a non-probabilistic sample of 20 participants. The data were analyzed using descriptive statistics with SPSS. The results show a high prevalence of paternal absence, associated with behavioral difficulties, emotional fragility, low school performance, and limitations in the socialization process of children. Simultaneously, high levels of emotional, economic, and social overload are observed in mothers in single-parent contexts. The results corroborate international literature and are supported by behaviorist, cognitive, and functionalist perspectives, demonstrating that paternal absence compromises essential mechanisms of psychosocial development. It is concluded that this phenomenon constitutes a significant factor of social vulnerability, and it is recommended that public policies supporting families and responsible parenting be strengthened.